Kebijakan Transformasi Digital Madrasah Aliyah Unggulan KH. Abd Wahab Hasbulloh Bahrul 'Ulum Tambakberas Jombang - Shobirin, Mochammad Syafiuddin; Qomar, Mujamil; Aziz, Abd (JoEMS (Journal of Education and Management Studies), 2023)
This research aims to analyze the digital transformation policy applied in Madrasah Aliyah Unggulan KH. Abd Wahab Hasbulloh Bahrul 'Ulum Tambakberas Jombang. This study uses a qualitative approach by conducting a case study of the madrasah. Methods used in this research include participatory observations, interviews with relevant stakeholders, and document analysis related to digital transformation policies. The results of the study showed that Madrasah Aliyah Unggulan KH. Abd Wahab Hasbulloh Bahrul 'Ulum has successfully implemented the digital transformation policy. The Madrasah has made significant changes in the use of information and communication technologies in learning and administrative activities. Some methods used in digital transformation include the implementation of e-learning, the use of school management software, and the utilization of social media for promotion and interaction with stakeholders. The digital transformation in the madrasah has had a positive impact, including improved accessibility of learning for students, administrative efficiency, and improved quality of learning. In addition, this madrasah also managed to leverage digital transformation to improve the image and reputation of the school. Despite its success, this study shows that there are some challenges in the implementation of digital transformation policies in Madrasah Aliyah Unggulan KH. Abd Wahab Hasbulloh Bahrul ‘Ulum. These challenges include the lack of adequate technological infrastructure, the limitations of digital knowledge and skills for some staff and teachers, and changes in organizational mindset and culture. This research provides insight into the experience of digital transformation in Madrasah Aliyah Unggulan KH. Abd Wahab Hasbulloh Bahrul 'Ulum Tambakberas Jombang. The results of this research can be a benchmark for other madrasahs in implementing successful digital transformation policies, as well as providing an understanding of the challenges that may be faced in the process.